Integration of Digital Technology in Effective and Adaptive English Learning - Ridayani, Ridayani; Sari, Fusvita (Journal of Innovative and Creativity, 2026)
Advances in digital technology have driven substantial transformations in the implementation ofEnglish language learning, so that its integration is no longer limited to the use of media alone, butis also directed at achieving effective learning that is responsive to students' needs. This studybegins with the fact that educators' abilities in implementing digital technology still show variation,which ultimately affects the quality of the process and outcomes of English language learning.This study aims to examine patterns of digital technology integration in English language learningand evaluate the level of effectiveness and adaptability of its application in the learning context. Aqualitative approach was used in this study, with data collection techniques including in-depthinterviews, observations of learning activities, and documentation covering learning tools and theuse of digital media. The research findings reveal that the use of digital technology, such as onlinelearning platforms, language learning support applications, and interactive media, contributes toincreasing student participation, expanding the variety of learning strategies, and facilitating thedevelopment of language skills contextually. The adaptability aspect is evident in teachers' abilityto adjust the use of technology to student characteristics, learning objectives, and the dynamics ofthe learning situation. The discussion shows that the success of digital technology integration islargely determined by teachers' pedagogical competence and digital literacy, accompanied byadequate learning environmental support. This study concludes that the integration of digitaltechnology that is designed systematically and reflectively is able to create effective and adaptiveEnglish learning, and makes a real contribution to improving the quality of learning and students'readiness to face the demands of the digital era.